Targeting glutamine metabolism as a potential target for cancer treatment - Wenxuan Zou; Zitao Han; Zihan Wang; Qian Liu (Journal of Experimental & Clinical Cancer Research)
Abstract Metabolic reprogramming is a hallmark of cancer cells, and the advent of “glutamine addiction” in numerous tumors signifies a pivotal advancement for precision-targeted therapy. This review demonstrates that glutamine metabolism is a pivotal factor in the development of malignant phenotypes in tumors by modulating multifaceted regulatory networks (Hippo/YAP, mTORC1 signaling pathway, and non-coding RNAs). These networks play a crucial role in the reprogramming of glutamine metabolism, which in turn affects various hallmarks of cancer, including cancer cell proliferation, ROS-mediated inhibition of apoptosis, and EMT-associated invasive metastasis. With respect to targeted therapeutic strategies, the focus on key transporters and metabolizing enzymes (ASCT2/GLS1) provides a theoretical foundation for the development of multi-targeted combination therapeutic regimens based on the inhibition of glutamine metabolism. A body of research has demonstrated that the metabolic processes of glutamine regulate a variety of immune system functions, including T cell depletion/activation, the polarization of TAMs, and the function of NK cells. This regulatory relationship, termed the metabolic-immune axis, is a crucial factor in the development of immune escape mechanisms by tumors. The study further suggests that a combination of targeted intervention strategies, involving the modulation of glutamine metabolism, has the potential to reshape the immune microenvironment and enhance the efficacy of CAR-T cell therapy. It is important to note that glutamine metabolism also affects tumor stroma formation by remodeling cancer-associated fibroblasts (CAFs). In response to therapeutic resistance mechanisms, tumor cells form adaptive escapes through ASNS and GAD metabolic branch activation, glucose/lipid metabolic compensation, and ATF4 transcriptional stress networks. This review systematically integrates the critical role of glutamine metabolism in tumor development and therapeutic resistance, providing new perspectives and translational pathways for the development of precision therapeutic strategy selection based on metabolic plasticity modulation.